Teacher's Professional Learning Practices During the Pandemic Period at St. Maria Assumpta - Filipa Bandut; Engelbertus Nggalu Bali; Stevanya Wollo; Yuliana Telik (Early Childhood Education Development and Studies (ECEDS), 2021)
The COVID-19 pandemic requires teachers to be sensitive and flexible in responding to any regulations issued by the government, especially regarding learning activities. All this is done to maintain and improve the quality of learning in the country. After the issuance of the Limited Face-to-face Learning (PTM) regulations, TK St. Maria Assumpta is enthusiastic and sees this as an opportunity to improve the quality of learning in their school. In this study, the researcher wanted to see how the professional learning practices of TK St. Kindergarten teachers were. Maria Assumpta during this pandemic. This study uses a qualitative method with the collection technique using observation and interviews.